Mapping the Learning Journey of Students and Parents in an Inclusive Music School: Case Study of Sunar Sanggita - Mahayasa, I Made Prasetya Wiguna; Ariyanti, Maya; Ghina, Astri (Journal Integration of Social Studies and Business Development, 2025)
This study analyzes customer journey mapping of parents and students in Sunar Sanggita, a social enterprise that empowers the blind as music teachers. Through a qualitative approach involving in-depth interviews with 16 respondents, this study identified the stages of the consumer journey and pain points associated with using inclusive music course services. The results reveal four primary pain points: a lack of transparency regarding information about blind teachers, concerns about teachers' abilities, dependence on teaching assistants, and a scarcity of events to motivate students. Despite the initial challenges, the majority of respondents appreciated the social value gained from the experience of learning with blind teachers. This research contributes to the development of empathy-based service strategies for social enterprises that empower people with disabilities, while also providing insights into enhancing the quality of the consumer experience in the context of inclusive music education.